Munigua, Spanien - Schattner, Thomas G.; Azcárraga Cámara, Sandra; Brose, K.; Bouresh, B.; Gutiérrez Rodríguez, Mario; Krug, Antje; Martini, Wolfram; Ruipérez, Heliodoro; Schäffler, D.; Scholz, Roman (e-Forschungsberichte des DAI, 2017)
Since more than 60 years the Madrid Department of the German Archaeological Institute has been conducting investigations at the Hispano-Roman municipium of Munigua. Current research focuses on a 3D-visualisation and reconstruction of the city. The project is accompanied by a thorough study of the function and use of the individual buildings in antiquity. During the campaigns of 2015 and 2016 the forum, the streets as well as the podium-temple of the city were analyzed. As a result, the voting process on the forum as well as the processional way through the city could be hypothetically reconstructed. A geophysical survey in the southern part of the city revealed the existence and structure of buildings.